MEDICINAL PLANTS AND THEIR USEFUL PROPERTIES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Medicinal plants are plants that have important medicinal properties for human health and are used for medicinal purposes. These plants are widely used from traditional medicine to the modern pharmaceutical industry. They can be wild or cultivated and help in the prevention and treatment of various diseases. Medicinal plants contain biologically active substances (vitamins, minerals, alkaloids, flavonoids and other chemical compounds) that have a beneficial effect on the body.